Yahoo Web Search

  1. Sort by

  1. If k-2 divides 2k, k-2 ≠ 0, then there is an integer i such that 2k = (k-2)i Solving for k gives... of i less than or equal to 1 that produce k≥ 3. Therefore the only ...

    1 Answers · Science & Mathematics · 20/03/2009

  2. Let K be a convex subset of R^p and let x,y be in the closure of K. Then there exist sequences (x_n), (y_n) of points in K such that lim x_n = x and lim y_n = y. The line segment between x_n and y_n...

    2 Answers · Science & Mathematics · 20/01/2012

  3. ∫(x = 0 to 1) x^k ln x dx = ∫(∞ to 0) (e^w)^k * w * (e^w...;==> x = e^w = -∫(w = 0 to ∞) we^((k+1)w) dw = -∫(w = 0 to ∞) we^((k+1)w) dw...1)t))] = (-1/(k+1)^2) * [1 + lim(t→∞) -e^((k+1)t)] = (-1/(k+1)^2) * (1 + 0), since k+1...

    3 Answers · Science & Mathematics · 10/06/2015

  4. k(k+1)(2k+1)/6 must be divisible by 100 means k(k+1)(2k+1) divisible by 600 which is 5x5x2x2x2x3 2k+1 is odd, and only one of k or k+1 can be even so you need k or k+1 divisible by 8 one of k, k+1, and 2k+1 will always be divisible...

    4 Answers · Science & Mathematics · 18/12/2013

  5. synthetic division 4 | 1 -k k 8 ---------------- .....1 4 | 1.. -k....... k............ 8 ...____4____4(4-k)_____4[k+4(4-k)] .....1.. 4-k....k+4(4-k)....0 According to last column, 8 + 4[k+4(4-k)] = 0 4[k+4(4-k)] = -8 4k + 16(4 - k) = -8 4k + 64 - 16k = -8 -12k = -72...

    1 Answers · Science & Mathematics · 09/11/2012

  6. ...you have written is evaluated like this: .030 = .22*(e^(-k))*(.005) I think you intended the exponent to be ((-k)*.005) so you should...

    1 Answers · Science & Mathematics · 28/09/2013

  7. y = x/(1 + kx) (1 + kx)y = x y + kxy = x kxy = x - y k = (x - y)/(xy) Say, this formula looks familiar!

    7 Answers · Science & Mathematics · 08/02/2010

  8. Decomposing 1/[k(k+1)(k+2)], you have: A/k + B/(k+1) + C/(k+2) = 1/[k(k+1.... Therefore: A(k+1)(k+2) + B(k)(k+2) + C(k)(k+1) = 1 which must hold true for all valid values of k. To determine...

    2 Answers · Science & Mathematics · 08/09/2007

  9. y = x/(1 + kx) y(1 + kx) = x y + kxy = x kxy = x - y k = (x - y)/(xy) I could have sworn I already answered this one!

    4 Answers · Science & Mathematics · 08/02/2010

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers